Evaluation of Gigantochloa scortechinii and soil interaction in three study sites in Malaysia - Mohamed, Johar; Abdul Hamid, Hazandy; Mohamed, Elizah; Mohamad Ismail, Fatin Norliyana; Abiri, Rambod; Jalil, Abdul Majid; Megat Wahab, Puteri Edaroyati; Moradi, Mostafa; Naji, Hamid Reza (Elsevier, 2022)
Understanding the productivity and physiological status of an organ (rhizome) function can lead into a sustainable production of sympodial bamboo. Nutrient elements and ash content (AC) are among the indicators to indicate the productivity and physiological status of an individual bamboo organ. The present study aimed to (a) determine the concentration of macronutrient elements of Gigantochloa scortechinii's rhizomes at four different ages collected at three study sites, and (b) investigate their relationship with AC. The destructive sampling was conducted on a set of four consecutive rhizomes using the selective random sampling method. Middle rhizome wall portion was used to determine the macronutrient elements and AC. All primary and secondary macronutrients were found to be different (p ≤ 0.01) at different study sites, except for the magnesium (Mg). The changes in nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and Mg from new sprout to mature rhizome showed a strongly positive relationship with AC. Thus, the N, P, K, Ca, and Mg concentrations decreased with rhizome age, resulting in a decrease in AC. The present study suggests that the suitable harvesting of individual bamboo culm and rhizome is at mature and older age while the remaining younger age bamboo is kept being grown so that the bamboo production is sustainable in terms of the physiological functions.